Improving the bacterial blight resistance of mestiso hybrid rice through gene pyramiding (The Philippine Journal of Crop Science, 2013)
The success of hybrid rice in increasing grain yield is hampered by its susceptibility to bacterial blight, which causes significant reduction in grain yield. This study aimed to determine the presence of introgressed resistance genes in improved maintainer and restorer parent lines; assess the genetic similarity of the improved parent lines to the original Mestizo 1 and Mestiso 3 parent lines; and evaluate disease resistance, grain quality and agronomic performance of the improved hybrids. With target gene selection, 21 backcross lines were confirmed to have 2-3 Xa genes, exhibiting high levels of resistance. Most of theses improved maintainer and restorer lines had recovered at least 80% of the recurrent parent genome based on genome-wide marker assay using simple sequence repeats. Cytoplasmic male-sterile lines were improved through repeated backcrossing to maintainer lines, with target gene selection and pollen sterility evaluation at each cycle. On-station and on-farm yield trials showed that the improved hybrids were disease resistant and comparable to the original hybrids with respect to morpho-agronomic traits and grain physico-chemical properties. The agreement between genotype and phenotype data indicate that resistance genes were successfully incorporated and the genetic background of recurrent parents were sufficiently recovered.